Proposed design of a Sustainable Heating System (SHS) using agricultural and livestock residual biomass for biogas production in high andean homes - Linares Nima, Luis Miguel (2025)
This study presents the design and evaluation of a Sustainable Heating System (SHS) that uses agricultural and livestock residual biomass as an energy source to heat a thermal fluid. The stored energy is used to climatize a 1 m² prototype dwelling, specifically designed for high Andean regions where low temperatures pose a challenge for thermal comfort. The system consists of a network of copper pipes arranged in a coil, connected to a storage tank where biomass combustion takes place, powered by gas generated from an external biodigester. The prototype dwelling was constructed using thermal insulating materials, such as gypsum boards and sheep wool, to optimize heat retention. Three scenarios were evaluated: a dwelling without insulation, a dwelling with insulation, and a dwelling with insulation plus the heating system. Results showed that the complete system implementation allowed the interior temperature to reach 4.1°C higher than local rural dwellings, demonstrating its effectiveness and ability to provide a more comfortable environment in cold climates. This SHS represents a viable and sustainable solution to improve thermal comfort in high Andean homes.